Perlindungan Hukum Terhadap Pelaku Perjanjian Adat Dalam Transaksi Utang Piutang Dan Dampaknya Dalam PerspektifHukum (Study Kasus Pada Unit Simpan Pinjam Masyarakat Di Desa Tenggak, Kecamatan Sidoharjo, Kabupaten Sragen) - Diantoro, Giyoto; , Septarina Budiwati, S.H. M.H; , Shalman Al-Farizi, S.H.,M.kn (2015)
Agreements customary in transactions of debts is an event in which two or more mutually pledge to bind themselves in an agreement made based debts customary law. Agreements customary in transactions of debts between units of savings and loan society to gulp borrowers money in the village, district. Sidoharjo, Kab. Sragen performed oral / unwritten and done without the special guarantee, in the form of property owned by the debtor. Agreements were made orally, was made because of lack of mutual trust between the two sides. Receivables debt agreements made orally permitted under the Act. In Article 1320-Civil Code, which contains the terms validity of a treaty, no requirement that requires that the agreement must be in writing. Agreements made legally juridical consequences and enactment as law for those who make it. The downside of an agreement made orally is if the debtor defaults and denied that there was any agreement will be difficult to prove the existence of the agreement of debts. Receivables debt agreements made with no specific guarantee in the form of property belonging to the debtor provide less legal protection for creditors the assurance that the debtors will pay off all debts. In the settlement of the problem of debts against the debtor in default is only done by way of negotiations, and it was never done with mediation or until the court tinggat. Handling problems if the debtor defaults is the billing / family approach kemasing troubled individual debtor, and if not successful it will be subject to customary that the debtor is scheduled to appear before all depositors in a forum, to ask for permission addition of repayment debts. For those who underestimate the debtor will be dealt with firmly, that the lender will conduct seizure of property belonging to the debtor is in default then pawn it or sell it to pay off all debts. If the settlement of the problem of debts by negotiating and / or the provision of a subpoena does not succeed, then it should be done with mediation, the mediator notes the existence of people who are experts in agreement debts. If mediation is not successful, then can be resolved through the courts. It is necessary to ensure justice and the rule of law between the parties to the dispute, with solutions based on positive law.